K.H. Hasyim Asy’ari’s Contribution to Indonesian Independence - Khuluq, Lathiful (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1998)
An important note that should be emphasized is that the physical history of the Indonesian revolution are rarely included the involvement of the clergy or religious leaders. The key role played by K.H. Hasyim through political fatwa, which is further supported by the widespread ideology of jihad in the war of independence, has contributed important sheet of the neglected history.DOI: 10.15408/sdi.v5i1.760